2013
DOI: 10.1128/aem.03704-12
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Internalization of Salmonella enterica in Tomato Plants

Abstract: bThe consumption of fresh tomatoes has been linked to numerous food-borne outbreaks involving various serovars of Salmonella enterica. Recent advances in our understanding of plant-microbe interactions have shown that human enteric pathogenic bacteria, including S. enterica, are adapted to survive in the plant environment. In this study, tomato plants (Solanum lycopersicum cv. Micro-Tom) grown in sandy loam soil from Virginia's eastern shore (VES) were inoculated with S. enterica serovars to evaluate plausible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 31 publications
(34 reference statements)
6
98
0
1
Order By: Relevance
“…into plant. Zheng et al (2013) also reported that Salmonella spp. has the ability to internalize into tomato plants through roots, leaves and blossoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…into plant. Zheng et al (2013) also reported that Salmonella spp. has the ability to internalize into tomato plants through roots, leaves and blossoms.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination can occur at any stage of production such as pre-harvest or post-harvest (Semenov et al 2010;Goldberg et al 2011;Bernstein 2011). Some recent studies reported internalization of bacteria into the plant part and subsequent translocation of bacteria to leaf and other aerial parts of the plant (Goldberg et al 2011;Zhuang et al 1995;Avila-Quezada et al 2010;Hirneisen et al 2012;Zheng et al 2013;Bernstein et al 2007a;Bernstein et al 2007b). This event is alarming due to the fact that internalization of pathogenic bacteria into fresh produce pose high risk to the consumers as they are significantly resistant to external biocidal washing agents (Ibarra-Sanchez et al 2004;Jablasone et al 2005;Donkor et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…내부로 침투할 능력이 있는 것으로 알려져 있다 9,10,11,12) . 또 한 Salmonella, E. coli O157:H7 등과 같은 병원성 미생물 이 과일 등에 오염이 된 후에는 세척 등으로 완전히 제거 하기가 어려우므로 13) , .…”
Section: Survey Of Microbial Contamination Of Tomatoes At Farms In Kounclassified
“…Several innovative approaches both chemically and physically have been explored for the decontamination of fresh or fresh-cut vegetables (Table 17.5). Effective washing and decontamination of fresh-cut veg etables is difficult to achieve due to the different types of vegetables, the inadequate efficacy of individual treatments alone (Table 17.5), the presence of biofilms on vegetables and on processing equipment (Jahid and Ha, 2012;Somers et al, 1994), and internalization/infil tration of bacteria within produce (Zhuang et al, 1995;Zheng et al, 2013;Takeuchi and Frank, 2000). Therefore, a combination of different disinfection methods (e.g., hurdle technology) (Rico et al, 2007;Joshi et al, 2013) is necessary to increase the efficacy of disinfectants against microbial population reduction.…”
Section: Bacteriamentioning
confidence: 99%